Optical and Electrical Characteristics of Fluorocarbon Films Deposited in a High-Density C4F8 Plasma - Kwon, Hyeokkyu; You, Sanghyun; Kim, Jun Hyun; Kim, Chang Koo (Korean Chemical Engineering Research, 2021)
− Optical and electrical characteristics of the fluorocarbon films deposited in a high-density C4F8 plasma under various source powers and pressures were investigated. The F/C ratio of the fluorocarbon film deposited in a high-density C4F8 plasma increased with increasing source power and decreasing pressure due to two-step deposition mechanism. The change in the F/C ratio of the film directly affected the optical and electrical characteristics of the fluorocarbon films deposited in a high-density C4F8 plasma. The refractive index of the fluorocarbon film increased with decreasing source power and increasing pressure contrary to the dependence of the film’s F/C ratio on the source power and pressure. This was because the increase in the F/C ratio suppressed electronic polarization and weakened the network structures of the film. The resistivity of the fluorocarbon film showed the same behavior as its F/C ratio. In other words, the resistivity increased with increasing source power and decreasing pressure, resulting from stronger repellence of electrons at higher F/C ratios. This work offers the feasibility of the use of the fluorocarbon films deposited in a high-density C4F8 plasma as an alternative to low dielectric constant materials because the optical and electrical properties of the fluorocarbon film can be directly controlled by its F/C ratio.
Keywords: F/C ratio; Fluorocarbon film; High-density plasma; Refractive index; Resistivity